Pemanfaatan Media Sosial Sebagai Alat Pemasaran dalam Meningkatkan Kinerja Usaha Kerajinan Perhiasan Desa Celuk- Sukawati, Kabupaten Gianyar -Bali - Nilna Muna (Departement of Mathematics Education, 2023)
The use of social media as a marketing tool to encourage the business performance of micro, small, and medium enterprises in jewelry crafts. This research is social media as a marketing tool for micro, small and medium enterprises (MSMEs) in the jewelry handicraft industry. The discussion was